2002
DOI: 10.1128/mcb.22.20.7134-7146.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Eukaryotic Initiation Factor 2 by Heme-Regulated Inhibitor Kinase-Related Protein Kinases in Schizosaccharomyces pombe Is Important for Resistance to Environmental Stresses

Abstract: Protein synthesis is regulated by the phosphorylation of the ␣ subunit of eukaryotic initiation factor 2 (eIF2␣) in response to different environmental stresses. One member of the eIF2␣ kinase family, hemeregulated inhibitor kinase (HRI), is activated under heme-deficient conditions and blocks protein synthesis, principally globin, in mammalian erythroid cells. We identified two HRI-related kinases from Schizosaccharomyces pombe which have full-length homology with mammalian HRI. The two HRI-related kinases, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 91 publications
2
58
0
Order By: Relevance
“…In particular, His-119 and Cys-409, the proposed heme axial ligands, are conserved only in mammals. Because the HRI homolog from Schizosaccharomyces pombe is not controlled by the heme iron (24), it is assumed that the heme-regulated HRI function is specific to mammals. In addition, erythroid differentiation in mammals is different from that in other vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, His-119 and Cys-409, the proposed heme axial ligands, are conserved only in mammals. Because the HRI homolog from Schizosaccharomyces pombe is not controlled by the heme iron (24), it is assumed that the heme-regulated HRI function is specific to mammals. In addition, erythroid differentiation in mammals is different from that in other vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in S. cerevisiae this post-translational event occurs at the onset of the stress response in a Gcn2/Ppk28-dependent manner (Mascarenhas et al, 2008). Another eIF2a kinase, Hri2, becomes also critical for survival upon long exposure of fission yeast cells to stress (Dunand-Sauthier et al, 2005;Zhan et al, 2002). Stress-induced activation of the Sty1 pathway triggers translation re-initiation by negatively regulating the closely related pathways of the Gcn2 and Hri2 kinases (Berlanga et al, 2010;Dunand-Sauthier et al, 2005).…”
Section: The Sty1 Regulatory Signals On Translationmentioning
confidence: 99%
“…2A). S. pombe possess, in addition to Gcn2, two other eIF2␣ kinases, Hri1 and Hri2 (33). We expressed GFP-YpkA in strains deleted for either of these kinases and found that YpkA sensitivity in hri1⌬ cells was comparable with wild-type cells (data not shown), whereas hri2⌬ cells were, like cells expressing eIF2␣(S52A), especially sensitive to YpkA (Fig.…”
Section: Resultsmentioning
confidence: 99%